Identification of resistant sources from Glycine max against soybean cyst nematode - Lian, Yun; Yuan, Ming; Wei, He; Li, Jinying; Ding, Binke; Wang, Jinshe; Lu, Weiguo; Koch, Georg (Frontiers in Plant Science, 2023)
Soybean cyst nematode (SCN, Heterodera glycines, HG) is one of the severe pests in plant-parasitic nematodes, which impairs root development and causes severe losses in soybean production worldwide. Breeding SCN-resistant cultivars is an important measure for securing harvests without affecting the environment as can be done with pesticides. The majority of genetic resources for plant pest resistances are found in wild or closely related species which are often difficult to use in breeding due to crossing barriers or close linkage with unfavorable agronomic traits. In this study, 12 soybean cultivars were evaluated for their marker haplotype at the rhg1 and Rhg4 SCN resistance loci and their SCN resistance tested against multiple races in environmentally-controlled bioassays. The results showed that all 12 cultivars displayed Peking-type resistance marker haplotypes and all of them proved to be resistant to multiple SCN races. These cultivars provide potential for improving H. glycines resistance of soybean as donor parent in breeding and could contribute to reduce SCN field populations as part of a sustainable agriculture management.